"Yes, we can!" review on team confidence in sports. (August 2017) - Fransen, Katrien; Mertens, Niels; Feltz, Deborah; Boen, Filip
Highlights: Collective efficacy and team outcome confidence are two types of team confidence. Team confidence is a dynamic construct that changes within a single game. This reviews discusses the sources and outcomes of team confidence. The current guidelines on how to measure team confidence are evaluated. Interesting avenues for future research are highlighted. Abstract : During the last decade, team confidence has received more and more attention in the sport psychology literature. Research has demonstrated that athletes who are more confident in their team's abilities exert more effort, set more challenging goals, are more resilient when facing adversities, and ultimately perform better. This article reviews the existing literature in order to provide more clarity in terms of the conceptualization and the operationalization of team confidence. We thereby distinguish between collective efficacy ( i.e., process-oriented team confidence) and team outcome confidence ( i.e., outcome-oriented team confidence). In addition, both the sources as well as the outcomes of team confidence will be discussed. Furthermore, we will go deeper into the dispersion of team confidence and we will evaluate the current guidelines on how to measure both types of team confidence. Building upon this base, the article then highlights interesting avenues for future research in order to further improve both our theoretical knowledge on team confidence and its application to the field.